On Absolute Continuity of Conjugations between Circle Maps with Break Points - Habibulla Akhadkulov; Mohd Salmi Md Noorani (Abstract and Applied Analysis)
Let T1 and T2 be piecewise smooth circle homeomorphisms with break points and identical irrational rotation numbers. We provide one sufficient and necessary condition for the absolute continuity of conjugation map between T1 and T2.